Relationship between intraperitoneal volume and intraperitoneal pressure during peritoneal dialysis—a pilot study in adult patients - Fansan Zhu; Laura Rosales Merlo; Lela Tisdale; Maricar Villarama; Jun Yi; Zahin Haq; Xiaoling Wang; Nadja Grobe; Karsten Fischer; Kulwinder Plahey; Richard A. Lasher; Paul Chamney; et al. (Physiological Reports, 2025)
Abstract Monitoring intraperitoneal pressure (IPP) offers valuable insights into changes of intraperitoneal volume (IPV) during peritoneal dialysis (PD). This study aims to investigate the relationship between IPV and IPP during a PD dwell. Thirteen patients were studied during a 2‐h dwell using 2 L of dialysate containing 2.5% dextrose. IPP was measured using a pressure sensor integrated into an automated PD cycler. IPV was monitored concurrently by segmental bioimpedance (Hydra 4200). The density (ρ) of the PD dialysate was measured using a meter, and the creatinine and glucose concentrations in both dialysate (D) and serum (P) were measured pre‐ and post‐PD dwell. A physical model (IPP = ρ × g × h), was used to describe the relationship between IPP and IPV, where h is the apparent dialysate height and g is the gravitational acceleration. The change in IPP (ΔIPP, −21.2 ± 18%) was mainly determined by the change of h (Δh, −20.9 ± 18.5%), while the change ρ (Δρ, −0.34 ± 0.06%), was minor. The study demonstrated an association between ΔIPP and the ratio of D/P creatinine and D/D0 glucose, suggesting that ΔIPP may reflect membrane transport characteristics. Due to its noninvasive and seamless nature, the clinical utility of PD cycler‐based measurement of IPP warrants further exploration.